2017
DOI: 10.1213/ane.0000000000001440
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Three-Dimensional Strain Imaging Identifies Reduction in Left Ventricular Function and Predicts Outcomes After Cardiac Surgery

Abstract: This study shows that cardiac surgery was associated with an acute reduction in postoperative left ventricular function, when evaluated with 3D strain imaging. In addition, preoperative 3D strain was demonstrated to be an independent predictor of acute and long-term clinical outcomes after cardiac surgery. The use of noninvasive 3D transthoracic echocardiogram strain imaging before cardiac surgery may provide added information to aid in perioperative risk stratification and management for these high-risk patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 36 publications
0
17
0
1
Order By: Relevance
“…In asymptomatic patients with moderate-severe aortic regurgitation, it was found that 3D global circumferential strain compensates for the reduction in 3D longitudinal strain for preserving the LVEF (56). Further supporting the clinical use of 3DSTE, 3D strain was reported to be an independent predictor of acute and long-term clinical outcomes after cardiac surgery (57). 3DSTE was feasible, reproducible and time saving for assessing LV systolic function in patients before and after transcatheter aortic valve implantation (58).…”
Section: Aortic Valve Diseasesmentioning
confidence: 88%
“…In asymptomatic patients with moderate-severe aortic regurgitation, it was found that 3D global circumferential strain compensates for the reduction in 3D longitudinal strain for preserving the LVEF (56). Further supporting the clinical use of 3DSTE, 3D strain was reported to be an independent predictor of acute and long-term clinical outcomes after cardiac surgery (57). 3DSTE was feasible, reproducible and time saving for assessing LV systolic function in patients before and after transcatheter aortic valve implantation (58).…”
Section: Aortic Valve Diseasesmentioning
confidence: 88%
“…Prior studies using preoperative and postoperative 3D strain measures demonstrate a reduction in LV function immediately after cardiac surgery. 10,12 In our study, we also provided information from two more time points, which are before and after grafting to further define when the LV function begins to change. There is a study reported that only excessive anterior motion of the posterior wall can be seen and overall LV function is not affected with changes in pericardial restraint after valvular and CABG surgery.…”
Section: Intraoperative Monitoring Of LV Performancementioning
confidence: 99%
“…The superiority of 3D STE over conventional 2D parameters has been shown when analyzing the complexity of LV mechanics. 12,32 But this technique requires offline analysis. Advances in 3D STE may overcome this limitation and help it step into clinical practice better.…”
Section: Limitationsmentioning
confidence: 99%
“…Three-dimensional strain and strain rate as parameters of myocardial deformation for the assessment of the left ventricle, right ventricle, and left atrium will play an important role in chamber quantification in the future [ 77 , 78 •].…”
Section: Cardiac Surgery and Three-dimensional Echocardiographymentioning
confidence: 99%